(untitled) (International Seven Journal of Multidisciplinary, 2025)
Aortic dissection is a cardiovascular emergency with high morbidity and mortality, whose early diagnosis remains challenging due to its variable and often nonspecific clinical presentation. This article aims to critically review contemporary evidence on aortic dissection, with emphasis on diagnostic challenges, emerging pathophysiological mechanisms, and current therapeutic strategies. This is a narrative literature review based on articles published over the past five years and selected from the PubMed database. The findings highlight the relevance of clinical suspicion combined with the timely use of computed tomography angiography, as well as the complementary role of biomarkers and risk stratification tools. Recent advances have expanded the understanding of the disease’s pathophysiology, demonstrating the involvement of inflammatory, immunological, and genetic pathways, in addition to new clinical scenarios, such as aortic changes associated with prolonged use of left ventricular assist devices. It is concluded that the integration of early diagnosis, advanced pathophysiological understanding, and individualized management is essential to reduce mortality and improve the care of patients with aortic dissection.